A Study Of The Effectiveness Of Guidance Service And Recidivism Rate Among Sungai Buloh Prisoners - Uthaya Kumar A/L Paramasiwan
Recidivism in prison is a problem that is frequently discussed because it affects other issues such as overcrowding, law changes, prison regulations, rising costs for security management, detention, and treatment, as well as the implementation of rehabilitation programmes. As we currently understand the institution, prison is more focused on rehabilitating, guiding, and educating offenders so that they can become disciplined and responsible people when they are released back into society. It is not just a place to punish those who do wrong. In Malaysia, the government's primary goal in attempting to lower crime rates is the rehabilitation of criminal offenders. In light of this, the government has emphasized the necessity of enhancing prison rehabilitation programmes in the Transformation Roadmap in order to lessen the propensity for repeat offences. This study aims to assess the guidance and counselling services provided to recidivists at Sungai Buloh Prison. The study gathered data from 254 participants (N=254) about the counselling services provided to inmates at Sungai Buloh Prison using qualitative and quantitative methods. The study sample was gathered using purposive and stratified random sampling methods. According to the research, there are a number of reasons why people end up in prison, including peer pressure, poor parental and educational support, low self-esteem, and poor parental support. The following services are available to prisoners: instruction in good behaviour, individual and group counselling, instruction in music careers, and self-help initiatives. The researcher discovered that this counselling service or activity is very helpful and successful in helping prisoners change their behaviour. The researchers suggested that prison guards be given counselling training so they can deliver counselling and rehabilitation services successfully. The study also urges the government to modify its ex-offender hiring practises because they should also be taken into account. Additionally, since prisons are intended to be correctional facilities, they must have more room for inmates to practise their self-help project skills.